The Assessment of the Maximum Heat Production and Cooling Effectiveness of Three Different Drill Types (Conical vs. Cylindrical vs. Horizontal) during Implant Bed Preparation—An In Vitro Study - Stefan Ihde (MDPI AG, 2021)
The aim of this experimental study was to verify thermal diffusion differences, by measuring the maximum temperature achieved with different drill shapes. Synthetic bone blocks of type I density made from solid rigid polyurethane (PUR) foam were used to perform the drilling procedures. The experiment was conducted at three different rotation speeds: 800, 3000 and 5000 rpm. Conical drills (with and without an internal cooling hole) were compared with horizontal drills and disc drills. The temperature during drilling for implant bed preparation was estimated with the use of thermocouples and an infrared (IR) camera. The temperature during drilling with disc cutters for lateral basal implants did not exceed 33 <semantics>∘</semantics>C and the temperature decreased in proportion to higher drill speed. The results indicate that the tested design is safe and will not cause bone overheating.